R. C. Wallace (1881-1955) - Legget, R.F. (ARCTIC, 1955)
By the death of Dr. Robert Charles Wallace on 30 January 1955, the Arctic Institute of North America lost more than its Executive Director. The staff and the Governors lost a warm friend. The north lost one who knew it well and who had served it faithfully in a variety of ways during his forty-five years in Canada. So well and so affectionately was he known as "Wallace of Queen's" that his links with the north of Canada were somewhat naturally overshadowed in the minds of many of his friends. To some it seemed strange that, after his distinguished service to Queen's University, and at a time in life when many men would have cast all official duties aside, he willingly accepted the invitation to serve the Arctic Institute in its senior administrative post. But those who knew him well were not surprised nor were they in any doubt that what was supposed to be a "half-time job" was to be for him a labour of love upon which no time limit could be imposed. .